2017
DOI: 10.5812/rijm.13929
|View full text |Cite
|
Sign up to set email alerts
|

Parent Training Based on the Choice Theory: Analysis of its Impact on Mothers’ Sense of Self-efficacy and their Conflicts with their Daughters

Abstract: Background: This research aimed to study the effectiveness of "parent training based on the Choice Theory" on the motherdaughter conflicts and increasing mothers' sense of self-efficacy. Methods: The quasi-experimental method was used to examine the research variables. The research population included a group of mothers of the students who were in sixth to ninth grade at Nure Narges school in region 5 of Tehran. The parent-adolescent conflict questionnaire (teen's papers) was used to assess the frequency and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2018
2018
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
1
0
1
Order By: Relevance
“…La autoeficacia de los cuidadores, no sólo influye sino que determina el estilo de crianza 45 . Se ha identificado que madres seguras respecto a la forma en que crían, generan mejores interacciones con sus hijos y contribuyen a la salud mental de los menores 46 . A este respecto, este estudio encontró que cerca de la mitad de los cuidadores tienen dificultades con su autoeficacia para ejercer su rol de crianza, especialmente los hombres y en zona rural.…”
Section: Discussionunclassified
“…La autoeficacia de los cuidadores, no sólo influye sino que determina el estilo de crianza 45 . Se ha identificado que madres seguras respecto a la forma en que crían, generan mejores interacciones con sus hijos y contribuyen a la salud mental de los menores 46 . A este respecto, este estudio encontró que cerca de la mitad de los cuidadores tienen dificultades con su autoeficacia para ejercer su rol de crianza, especialmente los hombres y en zona rural.…”
Section: Discussionunclassified
“…24 Group reality therapy increases person's motivation. 25 According to Glasser theory, person's behavior motivation is internal and is related to her/his impulses 26 persons can change their behavior after creating significant and effective internal evaluation of their control or choice system. 27 The other results of this research showed that there is a significant effectiveness from creativity therapy upon educational motivation score increasing.…”
Section: Discussionmentioning
confidence: 99%